2017
DOI: 10.1016/j.scr.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Generation of induced pluripotent stem cell (iPSC) line from a patient with triple negative breast cancer with hereditary exon 17 deletion of BRCA1 gene

Abstract: BRCA1 germline mutation confers hereditary predisposition for breast and ovarian cancer. To understand the physiopathology of mammary and ovarian epithelial cancer transformation, and to identify early driver molecular events, we have generated an iPSC line from a patient carrying a germline exon 17 deletion in BRCA1 gene (BRAC1Ex17 iPSC) in a high-risk family context. Blood cells were reprogrammed used non-integrative virus of Sendaï. The BRCA1-deleted iPSC had normal karyotype, harboured a deletion in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Hereditary cancers are due to oncogenic mutations or deletions and represent a major challenge in terms of diagnosis, prognosis, and prevention [1]. Recently, the development of the iPSC technology allowed these cancers to be modeled using patient-derived pluripotent stem cells [2,3,4]. It has been shown that this strategy can be used for modeling BRCA1-mutated breast cancer [5] and Li–Fraumeni syndrome with TP53 deletions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary cancers are due to oncogenic mutations or deletions and represent a major challenge in terms of diagnosis, prognosis, and prevention [1]. Recently, the development of the iPSC technology allowed these cancers to be modeled using patient-derived pluripotent stem cells [2,3,4]. It has been shown that this strategy can be used for modeling BRCA1-mutated breast cancer [5] and Li–Fraumeni syndrome with TP53 deletions [3].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our study was to evaluate the effect of BRCA1-deleted (BRCA1+/−) iMSCs on breast tumor development and progression, compared to iMSCs that contained two copies of BRCA1 (BRCA1+/+ iMSCs). The BRCA1+/− iMSCs used here were produced from iPSCs that were generated by reprogramming blood cells (PBMCs) from two patients with a heterozygous deletion of exon 17 of the BRCA1 gene [19].…”
Section: Discussionmentioning
confidence: 99%
“…Using PBMCs of these two affected family members and two normal (BRCA1 wildtype) individuals, we established a number of iPSC clones via non-integrating Sendai virus-based delivery of the four Yamanaka reprogramming factors: OCT4, SOX2, KLF4, and c-MYC [18]. In previous publications, we characterized the iPSCs generated from P2 [19] and confirmed the deletion of exon 17 in BRCA1 by multiplex ligation-dependent probe amplification analysis [20]. All iPSC clones generated from Patient 1 demonstrated human embryonic stem cell morphology and expressed pluripotency factors (NANOG, SOX2 and OCT4) as well as stem cell-specific surface markers (TRA-1-60 and SSEA4) (Figure S1A,B).…”
Section: Generation and Characterization Of Ipscs And Derivation Of Induced Mesenchymal Stem Cells (Imscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several iPSC lines have been established from patients with inherited cancer syndromes. These include those from patients harboring germline BRCA1 mutations predisposing to breast and ovarian cancers (Griscelli et al, 2017; Soyombo et al, 2013), from patients with neurofibromatosis type 1 (NF1) (Anastasaki et al, 2015; Wegscheid et al, 2018), and from those with Gorlin syndrome (Hasegawa et al, 2017). Directed differentiation strategies will enable researchers to use these lines to model development of the tissues that give rise to cancer in these syndromes.…”
Section: Considerations For Future Studies Using Stem Cells and Organmentioning
confidence: 99%